Evaluation of microplastic toxicity in accordance with different sizes and exposure times in the marine copepod Tigriopus japonicus. (January 2020) - Choi, Jin Soo; Hong, Sang Hee; Park, June-Woo
Abstract: The indiscriminate use of plastic has greatly increased microplastic contamination risk in the marine environment. Microplastics can affect all marine life via the food web, from primary producers (e.g., microalgae) to final consumers (e.g., carnivorous fish). Thus, several studies have attempted to evaluate microplastic toxicity, but information about the underlying mechanisms of their effect is limited. Therefore, in this study, we examined multiple factors that could contribute to microplastic-induced toxicity. We investigated the potential molecular effects of microplastic size and exposure time. We exposed the marine copepod Tigriopus japonicus to 50 nm and 10 μm polystyrene microbeads. We found that both size and exposure time increased intracellular levels of reactive oxygen species. In addition, antioxidant-related gene expression was modulated and antioxidant enzyme activities were changed significantly. The results of this study provide important insights into the molecular mechanisms of microplastic-induced toxicity in a marine organism. Highlights: Both 50 nm and 10 μm microplastics increased oxidative stress in T. japonicus. Smaller microplastics elevated ROS more than larger MPs. Molecular responses by toxicity of microplastics were differed according to the size and time.